Praktik Vegetarian Umat Buddha Theravada (Studi Kasus di Vihara Sasana Subhasita) - Nyoto Nyoto (STABN Sriwijaya, 2018)
In Buddha Dharma lesson by Buddha and then progress and known with by people around the world. After Parinibbana, Buddha Teachings In Buddha Dharma lesson by Buddha and then progress and known with by people around the world. After Buddha Parinibbana, Buddha Doctrine began to break and appear many sect in Buddhism. when there are 2 great sect known by buddhists, the sect is Mahayana and Theravada. Mahayana progress with based Buddha Dhamma but the progress followed the local culture and Theravada flourishes on the basis of the Buddha Dhamma. There is 2 difference that easy to known from sect practice, the costum is Mahayana doctrine are emphasize on vegetarian practice and Theravada not praticing vegetarian. Mahayana Sect practicing Bodhisatva moral principle and assume that every creature has the seed of Buddhahood. It is from this view that Mahayana practitioners do not consume food derived from murder. But in Theravada belief it is explained that every human being attain sanctity not seen from the food consumed, but from the effort in perfecting the parami. However there are some Sasana Subhasita Monastery, which is a monastery built by Sangha Theravada that practiced vegetarian diligently. Buddha Dhamma diajarkan oleh Sang Buddha dan kemudianberkembang dan dikenal manusia di seluruh penjuru dunia. Setelah Buddha Parinibbana ajaran Buddha mulai pecah dan muncul berbagai aliran dalam agama Buddha. Saat ada dua aliran besar yang dikenal oleh umat Buddha, yaitu Mahayana dan Theravada. Mahayana berkembang dengan berlandaskan Buddha Dhamma tetapi berkembang mengikuti budaya setempat dan Theravada berkembang dengan berlandaskan Buddha Dhamma. Ada dua perbedaan yang mudah dikenali dari kebiasaan aliran tersebut, yaitu aliran Mahayana menekankan pada praktik vegetarian, sedangkan Theravada tidak melaksanakan vegetarian. Aliran Mahayana menjalankan Bodhisatva Sīla dan menganggap bahwa setiap makhluk memiliki benih Kebuddhaan. Dari pandangan inilah maka para praktisi Mahayana tidak mengonsumsi makanan yang berasal dari pembunuhan. Akan tetapi, dalam keyakinan Theravada dijelaskan bahwa setiap manusia yang mencapai kesucian bukan dilihat dari makanan yang dikonsumsi, tetapi dari usaha dalam menyempurnakan parami. Umat Buddha di Wihara Sasana Subhasita yang merupakan wihara binaan Sangha Theravada Indonesia banyak yang melaksanakan vegetarian dengan tekun.